Mulḥaq fī Bayān Al-Fawā’id al-Nāfi’ah fī al-Jihād fī Sabīlillāh: Aktualisasi Jihad dan Purifikasi Azimat - Sidik Sidik (Manuskripta, 2015)
The term of jihad is often associated to radical and terrorist acts. As a result, the meaning of jihad into a dwarf, limited, and further potential countra-productive conditions in the community. Thus, it is important to reread ang reinterprate the meaning of jihad. One source that can be lifted is the text of Mulḥaq fī Bayān Al-Fawā’id Al-Nāí’ah fī Al-Jihād fī Sabīlillāh, which is attachment of the work of Shaykh Abdussamad al-Palimbani entitled Nasīḥāt al-Muslimīn wa Tadhkirāt al-Mukminīn fī Faḍā’il al-Jihād fī Sabīlillāh, which is written in 18th century. According to the text of Mulḥaq, jihad is a religious doctrine that must be actualized appropriate social context. In the context of the socio-political under colonial shackles, jihad in the form of physical resistance is a religious obligation, and it is notradicalism. This paper, therefore, trays to elaborate on the meaning of jihad itself, and on the other hand on the use of amulets as a source of power which is purified by reading verses of the Qur’an, prayer and remembrance. === Terma jihad sering diasosiasikan pada tindakan radikal dan teror. Akibatnya, makna jihad menjadi kerdil, terbatas, dan lebih lanjut berpotensi menimbulkan kondisi yang kontra produktif di masyarakat. Dengan demikian, teks terkait jihad menjadi penting dibaca dan dimaknai kembali. Salah satu sumber yang dapat diangkat adalah teks Mulḥaq fī Bayān Al-Fawā’id Al-Nāí’ah fī Al-Jihād fī Sabīlillāh, yang merupakan lampiran dari karya Syekh Abdussamad al-Palimbani yang berjudul Nasīḥāt al-Muslimīn wa Tadhkirāt al-Mukminīnfī Faḍā’il al-Jihād fī Sabīlillāh, yang ditulis pada abad ke-18 M. Berdasarkan naskah Mulḥaq, jihad merupakan merupakan doktrin keagamaan yang harus diaktualisasikan sesuai konteks sosialnya. Dalam konteks sosial politik di bawah belenggu penjajah, jihad dalam bentuk perlawanan fisik adalah suatu keharusan, dan itu bukanlah radikalisme. Tulisan ini, dengan demikian, mengelaborasipemaknaan jihad itu sendiri, dan di sisi lain tentang penggunaan azimat sebagai sumber kekuatan yang dipuriëkasi dengan bacaan ayat Al-Qur’an, doa dan zikir.